Analysis of Rooftop Solar Power Development in Northwest Vietnam using the Analytic Hierarchy Process - Le, Ngo Phuong; Giap, Giap Ngoc; Khanh, Nguyen Binh; Trung, Bui Tien; Phap, Vu Minh; Phi, Dai Hung (Engineering, Technology & Applied Science Research, 2024)
Traditional energy sources are gradually being exhausted, which causes many negative effects on the environment and contributes to the climate change. Countries around the world, including Vietnam, are focusing on developing renewable energy sources, such as solar power, to combat climate change and create a foundation for sustainable development. The development of solar power, particularly rooftop solar power, is being encouraged in various provinces and cities in Vietnam. The Northwest is a mountainous region in the Northern part of Vietnam with considerable solar energy potential. However, developing rooftop solar power projects requires balancing economic, technical, and environmental goals. Currently, there is no comprehensive research in Vietnam that fully evaluates the sustainable development goals for rooftop solar power in the Northwest region. This paper focuses on identifying the factors that influence the decision to install and use rooftop solar power in the Northwest region of Vietnam with the support of the Analytic Hierarchy Process (AHP) method and Expert Choice software. This impact ranges to varying degrees. The most significant influencing factor is the solar energy development policy, with a priority of 36.1%, while the social factor has the lowest priority value of 7.7%. The primary factor affecting people's decisions is the future solar power development policy, with a weight value of 24.2.